Polyclonal origin of colonic adenomas in an XO/XY patient with FAP. - Novelli, MR; Williamson, J; Tomlinson, I; Elia, G; Hodgson, S; Talbot, I; Bodmer, W; Wright, N (1996)
It is widely accepted that tumors are monoclonal in origin, arising from a mutation or series of mutations in a single cell and its descendants. The clonal origin of colonic adenomas and uninvolved intestinal mucosa from an XO/XY mosaic individual with familial adenomatous polyposis (FAP) was examined directly by in situ hybridization with Y chromosome probes. In this patient, the crypts of the small and large intestine were clonal, but at least 76 percent of the microadenomas were polyclonal in origin.